Analysis of mitochondrial respiration and ATP synthase in frozen brain tissues. Issue 3 (March 2023) - Yao, Pamela J.; Munk, Rachel; Gorospe, Myriam; Kapogiannis, Dimitrios
Abstract: Studying mitochondrial respiration capacity is essential for gaining insights into mitochondrial functions. In frozen tissue samples, however, our ability to study mitochondrial respiration is restricted by damage elicited to the inner mitochondrial membranes by freeze-thaw cycles. We developed an approach that combines multiple assays and is tailored towards assessing mitochondrial electron transport chain and ATP synthase in frozen tissues. Using small amounts of frozen tissue, we systematically analyzed the quantity as well as activity of both the electron transport chain complexes and ATP synthase in rat brains during postnatal development. We reveal a previously little-known pattern of increasing mitochondrial respiration capacity with brain development. In addition to providing proof-of-principle evidence that mitochondrial activity changes during brain development, our study details an approach that can be applicable to many other types of frozen cell or tissue samples. Highlights: Workflow for measuring mitochondrial respiration in frozen tissues and cells. Uses small sample amount and commercially available reagents. Proof-of-principle experiment reveals respiration pattern in developing rat brain. Applicable to animal and human samples, bridging basic science and clinical studies.